2022
DOI: 10.1002/adma.202107940
|View full text |Cite
|
Sign up to set email alerts
|

A Two‐Pathway Model for the Evolution of Colloidal Compound Semiconductor Quantum Dots and Magic‐Size Clusters

Abstract: A fundamental understanding of formation pathways is critical to the controlled synthesis of colloidal semiconductor nanocrystals. As ultrasmall‐size quantum dots (QDs) sometimes emerge in reactions along with magic‐size clusters (MSCs), distinguishing their individual pathway of evolution is important, but has proven difficult. To decouple the evolution of QDs and MSCs, an unconventional, selective approach has been developed, along with a two‐pathway model that provides a fundamental understanding of product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
79
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 33 publications
(85 citation statements)
references
References 71 publications
5
79
0
Order By: Relevance
“…Then, they were mixed at room temperature; CdTeSe MSC-399 developed during the room-temperature incubation of the resultant mixture. We suggested that similar to binary MSCs, ternary CdTeSe MSC-399 also evolved from its counterpart PC, ternary CdTeSe PC-399, and PC-399 was produced via the substitution reaction of the CdTe PC and CdSe Mo/Fr . During the mixture incubation, PC-399 formed with a relatively fast rate and then transformed to MSC-399 at a relatively slow speed.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Then, they were mixed at room temperature; CdTeSe MSC-399 developed during the room-temperature incubation of the resultant mixture. We suggested that similar to binary MSCs, ternary CdTeSe MSC-399 also evolved from its counterpart PC, ternary CdTeSe PC-399, and PC-399 was produced via the substitution reaction of the CdTe PC and CdSe Mo/Fr . During the mixture incubation, PC-399 formed with a relatively fast rate and then transformed to MSC-399 at a relatively slow speed.…”
mentioning
confidence: 96%
“…Colloidal II–VI metal (M) and chalcogenide (E) semiconductor magic-size clusters (MSCs) have their own special precursor compounds (PCs). While MSCs display sharp optical absorption at constant wavelengths, their counterpart PCs are transparent at these and longer wavelengths. The idea that MSCs evolve from their corresponding PCs via intramolecular reorganization is present in the two-pathway model that provides an in-depth understanding of the growth relation between binary ME MSCs and binary colloidal semiconductor ME quantum dots (QDs) (Scheme S1a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first report of CdS magic-size clusters (MSCs) by Henglein and his co-workers in the reaction of Cd(ClO 4 ) 2 and H 2 S in 1984, 1 MSCs composed of discrete numbers of atoms have also been found to exist in the pre-nucleation stage of quantum dots (QDs). 2–7 Colloidal MSCs are considered to be crucial in describing how nanomaterials evolve from molecules and nanocrystals, 8–12 and they are commonly employed as precursors for preparing functional nanomaterials, such as QDs, 13,14 nanowires, 15 nanosheets, 16–18 nanorods 19 and nanoribbons. 18–21 Moreover, MSCs also demonstrate their potential applications in single-component white-light emitters 22–26 and ultrasmall colloidal dilute magnetic semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been proposed that dMSC-393 and dMSC-460 have their corresponding precursor compounds (PCs), and PC-393 is formed in reactions first. The PCs and their counterpart MSCs have similar core masses, while the former is optically transparent; their transformations are reversible via intramolecular reorganizations. For the transformation from CdSe dMSC-393 to dMSC-460, a PC-enabled pathway has been proposed, which involves three key steps. dMSC-393 transforms first to PC-393.…”
mentioning
confidence: 99%